Seepage Behavior of Fractures in Paleogene Sandstone Reservoirs in Nanpu Sag, Bohai Bay Basin, Eastern China - Wang, Zhaosheng; Muhtar, Meiri; Xu, Donghao; Fang, Jinchuan; Li, Jing; Liu, Daojie; Zhang, Zhenguo; Gao, Lianfeng (Frontiers in Earth Science, 2021)
Natural fractures play an important role in the seepage system of Paleogene sandstone reservoirs at Nanpu Sag. Characteristics and formation mechanisms of natural fractures and stress-sensitivity permeability are comprehensively investigated and their impact on water injection is discussed based on core and log data (FMI and diplog data) as well as stress-sensitivity permeability measurement. Results show that high-angle shear fractures, including NE-SW strike fractures and NW-SE strike fractures, are widely developed in the study area, which were primarily developed during the late Paleogene and late Neogene. The present maximum horizontal principal stress is orientated at N60°–80°E, approximately parallel to the NE-SW fractures, contributing greatly to the seepage system at the early oilfield development stage. Fractures in the study area can be divided into three phases and are characterized by obvious stress-sensitivity permeability, which is closely related to fracture aperture and throat size. Since the fracture occurrence enhances stress sensitivity of permeability, it is necessary to regulate well pattern based on dynamic behaviors of fractured reservoirs at different development stages.